(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
The role of infrastructural facilities in increasing the productive potentials and livelihood activities of rural populace has never been in doubt. Against this background therefore, the study, examined the state of infrastructural facilities provisions and effect on livelihood activities of rural dwellers in Katsina State, Nigeria. Multi-stage sampling technique was used to select 224 respondents. Structured interview schedule was used to collect information on respondents’ socio-economic characteristics, availability and conditions of rural infrastructural facilities, livelihood activities, constraints and perceived effect of rural infrastructural facilities. The data were analysed using descriptive statistics and inferential statistics. Most respondents were within 21-30 years of age, married, and had Quranic education and farming as primary occupation. Skills acquisition centres, storage facilities and secondary schools were among non-available infrastructural facilities while processing centres, storage and skills acquisition centres were in poor conditions. Levels of involvements in non-farm and off-farm/processing activities were low while high for agricultural activities. Most respondents’ overall level of perception on effect of infrastructural facilities on their livelihood activities was low. Also, levels of perceptions of the effect of infrastructural facilities on non-farm and off-farm/processing activities were low while level of perception on agricultural activities was high. Significant relationships existed between sex (χ2 =58.017, <p = 0.05), household size (χ2 = 5.393, <p = 0.05) and respondents’ perceived effect of infrastructural facilities. Also, significant correlations existed between age (r = 0.143, access (r = -0.232), condition (r = -0.130), constraints (r = 0.143) and respondents’ perceived effect of infrastructural facilities on their livelihood activities. Low effect of infrastructural facilities was informative to the abysmal level of infrastructural provisions and state of available ones in the area. Providing infrastructural framework based on people’s felt needs and implementing same accordingly is germane to improved livelihood activities in the area.